Observation of ultraviolet photothermoelectric bipolar impulse in gallium-based heterostructure nanowires - Jinjie Zhu; Qing Cai; Pengfei Shao; Shengjie Zhang; Haifan You; Hui Guo; Jin Wang; Junjun Xue; Bin Liu; Hai Lu; Youdou Zheng; Rong Zhang; et al. (Nature Communications)
Abstract The incorporation of thermal dynamics alongside conventional optoelectronic principles holds immense promise for advancing technology. Here, we introduce a GaON/GaN heterostructure-nanowire ultraviolet electrochemical cell of observing a photothermoelectric bipolar impulse characteristic. By leveraging the distinct thermoelectric properties of GaON/GaN, rapid generation of hot carriers establishes bidirectional instantaneous gradients in concentration and temperature within the nanoscale heterostructure via light on/off modulation. The thermoelectromotive force induced by these gradients, combined with the type-II heterojunction band structure, facilitates carrier transport, resulting in transient bidirectional photothermal currents. The device achieves exceptional responsivity (17.1 mA/W) and remarkably fast speed (8.8 ms) at 0 V, surpassing existing semiconductor electrochemical cells. This bipolar ultraviolet impulse detection mode harnesses light-induced heat for electricity generation, enabling innovative bidirectional encryption communication capabilities. Anticipated applications encompass future sensing, switchable light imaging, and energy conversion systems, thereby laying a foundation for diverse optoelectronic technological advancements.